A Polymorphism in Hepatocyte Nuclear Factor 1 Alpha, rs7310409, Is Associated with Left Main Coronary Artery Disease - Rui Liu; Hanning Liu; Haiyong Gu; Xiao Teng; Yu Nie; Zhou Zhou; Yan Zhao; Shengshou Hu; Zhe Zheng (Biochemistry Research International)
Coronary artery disease is the leading cause of mortality and morbidity in the world. Left main coronary artery disease (LMCAD) is a particularly severe phenotypic form of CAD and has a genetic basis. We hypothesized that some inflammation- and hyperhomocysteinemia-related gene polymorphisms may contribute to LMCAD susceptibility in a Chinese population. We studied the association between polymorphisms in the genes hepatocyte nuclear factor 1 alpha (HNF1A; rs7310409, G/A), C-reactive protein (rs1800947 and rs3093059 T/C), methylenetetrahydrofolate reductase (rs1801133, C/T), and methylenetetrahydrofolate dehydrogenase (rs1076991, A/G) in 402 LMCAD and 804 more peripheral CAD patients in a Chinese population. Genotyping was performed using the matrix-assisted laser desorption/ionization time-of-flight mass spectrometry method. When the HNF1A rs7310409 GG homozygote genotype was used as the reference group, both the individual, GA and AA, and combined GA/AA genotypes were associated with an increased risk of LMCAD. This single nucleotide polymorphism (rs7310409) is strongly associated with plasma CRP levels. In conclusion, the present study provides evidence that the HNF1A rs7310409 G/A functional polymorphism may contribute to the risk of LMCAD.